1987
DOI: 10.1093/schbul/13.3.357
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Process-reactive Dimension

Abstract: Harrow et al. (1986) report the limitations of the process-reactive dimension as a long-term outcome predictor for young, early phase DSM-III schizophrenics. Two additional studies are now described contrasting the good success of the process-reactive approach as a short-term predictor with DSM-II schizophrenia to its poor success in the same mode with DSM-III schizophrenics. The point is made that the change in diagnostic methods has reduced the heterogeneity of the current population of schizophrenics. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…Haas et al), which confers a better outcome than schizophrenia or schizoaffective disorder. Thus, our findings support suggestions (4,5) that the inclusion of a 6-month duration of illness criterion for DSM-III-R and, subsequently, DSM-IV diagnoses would eliminate much if not all of the predictive effect seen in earlier studies of onset of psychosis. Although three studies (12, 21; unpublished 1994 paper by G.L.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Haas et al), which confers a better outcome than schizophrenia or schizoaffective disorder. Thus, our findings support suggestions (4,5) that the inclusion of a 6-month duration of illness criterion for DSM-III-R and, subsequently, DSM-IV diagnoses would eliminate much if not all of the predictive effect seen in earlier studies of onset of psychosis. Although three studies (12, 21; unpublished 1994 paper by G.L.…”
Section: Discussionsupporting
confidence: 82%
“…That study, which used ICD-9 and the computer algorithm CATEGO to define the diagnostic categories, found onset type to be one of the two most important predictors of 2-year outcome (the other was settingi.e., developed versus developing country). However, in the mid-1980s, retrospective studies found that the 6-month duration of illness criterion required for the DSM-III diagnosis of schizophrenia reduced the number of patients considered to have an acute onset, making it more difficult to predict outcome in young patients with recent-onset schizophrenia (4,5).…”
mentioning
confidence: 99%
“…A key issue is the extent of heterogeneity in schizophrenia as defined by DSM-II and DSM-III . Herron (1987) and others have observed that DSM-III schizophrenia appears to be composed of process schizophrenics to a greater extent than was DSM-II schizophrenia. Indeed, recent research suggests that DSM-III schizophrenics are more likely to be a more homogeneous, “poor prognosis” group as defined by the classical prognostic indicators of Vaillant and Stephens (Westermeyer and Harrow 1984).…”
Section: Do Narrow Concepts Of Schizophrenia Such As That Found In Th...mentioning
confidence: 91%
“…If these subtypes or dimensions are meaningful, then one might find that they separate schizophrenics according to their prognosis, course or outcome, or some other major factors (e.g., biological subtypes, family-genetic background, and parental home environment). Herron (1987) focuses on the process-reactive dimension, one of the major ways of subtyping schizophenia. This key dimension has been the subject of extensive research (Kantor and Herron 1966; Garmezy 1970; Higgins 1971), and has been invoked in theories about the origin of schizophrenia (Rodnick and Garmezy, 1957).…”
Section: Do Narrow Concepts Of Schizophrenia Such As That Found In Th...mentioning
confidence: 99%
See 1 more Smart Citation